BIOCHEMICAL PROFILE AND ANTIMICROBIAL ACTIVITY OF A CYANOBACTERIUM, SCYTONEMA TOLYPOTHRICHOIDES ISOLATED FROM ACIDIC RICE FIELD SOIL OF CACHAR DISTRICT (ASSAM), INDIA: Life Sciences-Ecology - SHOUBHONIK DEB; JAYASHREE ROUT; MAHUYA SENGUPTA; BISWAJIT CHAKRABORTY (International Journal of Life Science and Pharma Research, 2022)
Scytonema tolypothrichoides, a filamentous cyanobacterium, has been isolated from acidic rice field soil from Dholai area of Cachar district in Assam, North-East India. The growth rate determination and biochemical analysis of chlorophyll a (Chl-a), total carotenoid content (TCC), phycobiliproteins, total proteins (PRT), total carbohydrates (CHO), and exopolysaccharides (EPS) were carried out. The algal strain had a higher phycocyanin content than those of other pigments. The nitrogen fixation potential of the alga has also been ascertained. Antimicrobial studies against some selected microbial strains revealed moderate activity.